Optimization of Pectin Extraction from Kepok Banana Peel (Musa Acuminata Balbisiana Colla) Using Natural Deep Eutectic Solvent (NADES) - Ahmad Fauzan; Ghusrina Prihandini; Angga Yudha W N; Rivan Sihaloho (Department of Chemical Engineering, Politeknik Negeri Bandung, 2023)
Kepok banana peel is an abundant waste used as the main ingredient in pectin extraction. The pectin contained in Kepok bananas is known to be at a fairly high level compared to other types of bananas. This study aimed to determine the water content, methoxyl content, equivalent weight, galacturonic acid, and pectin yield in the pectin extraction process using the NADESS solvent extraction method at various NADESs C molar ratios (1:4; 1:7; 1:20). ), and extraction temperature (80oC, 90oC, 100oC). based on the results obtained, the best extract located at a ratio of 1:4 with a temperature of 90oC, with a moisture content of 99.8%, methoxyl content of 2.79%, yield of pectin of 5.81%, an equivalent weight is 5333.33, and the galacturonic acid content is 75.56%. While the test results show that the concentration of the given K: G solution affects the amount of pectin yield obtained in this extraction process.